The Additive Effect of Rosmarinic Acid for The Reduction of Glomerular NF-kB Expression in Diabetes Rat that was given Telmisartan - Fachrureza, Mochamad; Samsu, Nur; Rudijanto, Achmad (Jurnal Penyakit Dalam Indonesia, 2019)
Introduction. Diabetic nephropathy is one of the common complications of diabetes, which one of its causes is the increase of free radicals through the activation of NF-kβ and Angiotensin II. Rosmarinic acid has the activity as the anti-oxidant and anti-inflammatory, and the telmisartan is the partial PPAR-γ agonist that has the anti-fibrotic effect. This study aimed to identify the effect of rosmarinic acid and telmisartan in the reduction of subunit p65 NF-kB expression on the glomerular diabetes rat. Methods. An experimental study with a post-test only controlled group was conducted in a group of rats (Rattus norvegicus). Rats were randomly divided into five groups (n=3-4 per group): three treatment groups (group 1: rosmarinic acid 75 mg/kg/ day; group 2: telmisartan 1 mg/kg/day, group 3: combination of rosmarinic acid 75 mg/kg/day and telmisartan 1mg/kg/ day per day), and two control groups (negative and positive control group). After eight weeks, rats were dissected. Blood sugar more than 270 mg/dl confirmed that the rats in diabetes state. The measurement of albuminuria was done using ELISA and the expression of subunit p65 NF-kβ using the immunofluorescence method. Results. The expression of subunit p65 NF-kβ in negative control group was 519.70 (SD 158.12), 702.19 (SD 189.69) in positive control group, 631.19 (SD 119.21) in the rosmarinic acid group, 355.68 (SD 44.71) in the telmisartan group, and 572.37 (SD 98.09) in the combination group (p<0.001). The post hoc test showed that the mean value of subunit p65 NF-kβ expression was significantly different between the positive control group and the telmisartan group (p<0.001). But, there was no significant mean difference of subunit p65 NF-kβ expression between the positive control group and the rosmarinic acid group (p=1.000), as well as between the combination rosmarinic acid and telmisartan group. Conclusion. The addition of telmisartan can reduce expression of the subunit p65 NF-kB. However, adding the rosmarinic acid in diabetes rats given telmisartan did not reduce the expression of subunit p65 NF-kB in the same level with the negative control group.